The Three-Dimensional Morphology of Femoral Medullary Cavity in the Developmental Dysplasia of the Hip - Zhang, Min; Liu, Bo-Lun; Qi, Xin-Zheng; Yang, Qing-Qing; Sun, Jing-Yang; Zheng, Qing-Yuan; Zhang, Guo-Qiang; Cheng, Cheng-Kung (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: This study aimed to assess the morphology of the femoral medullary canal in subjects with developmental dysplasia of the hip (DDH) with the intent of improving the design of femoral stems in total hip arthroplasty. Methods: Computed tomography images of 56 DDH hips, which were classified into Crowe I to Crowe IV, and 30 normal hips were collected and used to reconstruct three-dimensional morphology of the femoral medullary cavity. Images of twenty-one cross sections were taken from 20 mm above the apex of the lesser trochanter to the isthmus. The morphology of femoral cavity was evaluated on each cross section for the longest canal diameter, the femoral medullary torsion angle (FMTA), and the femoral medullary roundness index (FMRI). Results: The Crowe IV group displayed the narrowest medullary canal in the region superior to the end of the lesser trochanter, but then gradually aligned with the medullary diameter of the other groups down to the isthmus. The FMTA along the femoral cavity increased with the severity of DDH, but the rate of variation of FMTA along the femoral canal was consistent in the DDH groups. The DDH hips generally showed a larger FMRI than the normal hips, indicating more elliptical shapes. Conclusion: A femoral stem with a cone shape in the proximal femur and a cylindrical shape for the remainder down to the isthmus may benefit the subjects with severe DDH. This design could protect bone, recover excessive femoral anteversion and facilitate the implantation in the narrow medullary canal.